2014
DOI: 10.1097/bot.0b013e31829e7358
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Closed Intramedullary Nailing for Intra-articular Distal Tibial Fractures

Abstract: Therapeutic level IV. See instructions for authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…During surgery, the guide wire must be carefully placed through the center of the coronal and sagittal planes of the ankle. [2] Fixation of the fibula in distal tibial fractures is also a controversial topic. Egol et al [16] found a late malalignment rate of 4% in distal tibial fractures treated with fibular fixation and of 13% in distal tibial fractures treated without fibular fixation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…During surgery, the guide wire must be carefully placed through the center of the coronal and sagittal planes of the ankle. [2] Fixation of the fibula in distal tibial fractures is also a controversial topic. Egol et al [16] found a late malalignment rate of 4% in distal tibial fractures treated with fibular fixation and of 13% in distal tibial fractures treated without fibular fixation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Intramedullary nailing and fixation with plate and screws are the most preferred methods of treatment for extra-articular distal tibia fractures. Both treatment methods have advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations